2017
DOI: 10.3945/jn.117.247437
|View full text |Cite
|
Sign up to set email alerts
|

Excretion of Zinc and Copper Increases in Men during 3 Weeks of Bed Rest, with or without Artificial Gravity

Abstract: Zinc and copper have many physiologic functions and little or no functional storage capability, so persistent losses of either element present health concerns, especially during extended-duration space missions. We evaluated the effects of short-term bed rest (BR), a spaceflight analog, on copper and zinc metabolism to better understand the role of these nutrients in human adaptation to (simulated) spaceflight. We also investigated the effect of artificial gravity on copper and zinc homeostasis. Zinc and coppe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…87 Copper excretion increases during bedrest. 88 Kidney disease, coeliac disease and bariatric surgery all increase the requirement for copper. 89–91 The prevalence of these conditions in the population is high, and copper deficiency may masquerade as other conditions, such as myelodysplastic syndrome, and go unrecognised.…”
Section: Introductionmentioning
confidence: 99%
“…87 Copper excretion increases during bedrest. 88 Kidney disease, coeliac disease and bariatric surgery all increase the requirement for copper. 89–91 The prevalence of these conditions in the population is high, and copper deficiency may masquerade as other conditions, such as myelodysplastic syndrome, and go unrecognised.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Cu excretion was notably higher in Japanese women with itai-itai disease, compared with women in a control group, but Zn excretion was not increased by Cd exposure in either group [26]. In a study that examined another form of stress as artificially low gravity, simultaneous increases in Zn and Cu excretion were observed in men [34]. In an experimental study, high urinary Cu excretion seen in Wilson's disease, a genetic disorder resulting in excessive hepatic Cu accumulation, was a mechanism to remove Cu through upregulation of a 2kDa small copper carrier (SCC) that transports Cu to kidneys [35].…”
Section: Discussionmentioning
confidence: 94%
“…8 weeks of acupuncture treatment was shown to increase iron absorption compared to control group (27). In another study, 3 weeks of bed rest increased Zn and Cu excretion (28). Therefore it can be suggested that acrylamide may interfere with mechanisms other than diet and altered Zn, Cu and Pb absorption and excretion.…”
Section: Discussionmentioning
confidence: 95%